PERBANDINGAN PENGARUH LATIHAN LADDER DRILL: ONE FOOT EACH SQUARE DAN LATIHAN LADDER DRILL: TWO FEET EACH SQUARE TERHADAP KECEPATAN LARI 60 METER PADA TIM SEPAKBOLA SMK TARUNA PEKANBARU - Robbi Darwis; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTResult the identification of the problem shows that pekanbaru’s taruna vocationalhigh school of football team not have a good running speed. This is due to lack ofexecise leads to psysical condition especially speed. Therefore, this study aimedto compare the significan influence of ladder drill: one foot each square andladder drill: two feet each square to speed run 60 meters at Pekanbaru’s Tarunavocational high school of football team.This research is experimental research. The research conducted on Pekanbaru’sTaruna vocational high school of football team. Data were obtained and collectedthrough the pretest and posttest before and after ladder drill: one foot eachsquare and ladder drill: two feet each square. Data was analyzed deskriftive.Result of A group t test analyzes yield of 6,96 and B generate group with a yieldof 7,73 with t tabel 1,869 at significan level of 0,05, while group A and group Bwith a yield of 4,21 t tabel 1,764 at significant level 0,05. So that the thirdhypotesis is accepted. It can be concluded that there is a signifikan effect ofcomparison between ladder drill: one foot each square and ladder drill: two feeteach square to speed run 60 meters at Pekanbaru’ Taruna vocational high schoolof football team. Hence the increas in the average ladder drill: two feet eachsquare more significant effect on running speed of 60 meters.Keywords: Exercise ladder drill: one foot each square and ladder drill: two feeteach square, Speed run 60 meters.